Analysis of Indonesian Mathematics Teachers’ Ability in Applying Authentic Assessment - Pardimin Pardimin (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The 2013 curriculum implies the use of authentic assessment that emphasizes on the assessment of students' readiness aspects, processes and students’ learning outcomes as a whole. The integration of the assessment of the three components will demonstrate the students' capacity, style, and learning achievement. It is important for mathematics teachers to have the ability to conduct assessments of learning and to utilize the results of those assessments for the purposes of mathematics learning. This study aims to: (1) analyze the profile of the ability of the mathematics teachers in carrying out the authentic assessment, (2) find out the profile of the mathematics teachers’ ability to apply authentic assessment results, and (3) know the constraints of the mathematics teachers in developing the authentic assessment. This research uses a quantitative descriptive method involving junior high school teachers in Yogyakarta Indonesia. Data were collected using questionnaires and triangulated with documentation and Focus Group Discussion (FGD). The results show that the ability of the junior high school teachers in Yogyakarta in applying and using the results of authentic assessment was relatively good. The teachers used authentic assessment information to design remedial and enrichment programs. This study also reveals that the teachers still experienced difficulties in developing authentic assessment instruments. Keywords: authentic assessment, teachers’ ability, mathematics teachers, Curriculum 2013Analisis Kemampuan Guru Matematika di Indonesia Dalam Menerapkan Penilaian Otentik Abstrak: Kurikulum 2013 mengisyaratkan penggunaan penilaian otentik yang menekankan penilaian pada aspek kesiapan, proses, dan hasil belajar siswa secara utuh. Keterpaduan penilaian ketiga komponen tersebut akan menggambarkan kapasitas, gaya, dan perolehan belajar siswa. Penting bagi guru matematika untuk memiliki kemampuan menyelenggarakan penilaian terhadap pembelajaran serta memanfaatkan hasil penilaian tersebut untuk kepentingan pembelajaran matematika. Penelitian ini bertujuan untuk: (1) menganalisis profil kemampuan guru matematika dalam melaksanakan penilaian otentik, (2) profil kemampuan guru matematika dalam menerapkan hasil penilaian autentik, dan (3) mengetahui hambatan-hambatan dari guru matematika dalam mengembangkan penilaian otentik. Penelitian menggunakan metode deskriptif kuantitatif yang melibatkan guru matematika SMP di Yogyakarta Indonesia. Data dikumpulkan dengan menggunakan kuesioner dan dilakukan triangulasi dengan dokumentasi dan Focus Group Discussion. Hasil penelitian menunjukkan bahwa kemampuan guru SMP di Yogyakarta untuk menerapkan dan menggunakan hasil penilaian otentik relatif baik. Guru telah menggunakan informasi hasil penilaian otentik untuk mendesain program remedial dan pengayaan. Studi ini juga mengungkapkan bahwa para guru juga masih mengalami kendala dalam mengembangkan instrumen penilaian otentik. Kata Kunci: penilaian otentik, kemampuan guru, guru matematika, Kurikulum 2013